The L‐α‐Lysophosphatidylinositol/G Protein–Coupled Receptor 55 System Induces the Development of Nonalcoholic Steatosis and Steatohepatitis. Issue 2 (13th November 2020) - Fondevila, Marcos F.; Fernandez, Uxia; Gonzalez‐Rellan, Maria J.; Da Silva Lima, Natalia; Buque, Xabier; Gonzalez‐Rodriguez, Agueda; Alonso, Cristina; Iruarrizaga‐Lejarreta, Marta; Delgado, Teresa C.; Varela‐Rey, Marta; Senra, Ana; Garcia‐Outeiral, Vera; et al.
Abstract : Background and Aims: G protein–coupled receptor (GPR) 55 is a putative cannabinoid receptor, and l‐α‐lysophosphatidylinositol (LPI) is its only known endogenous ligand. Although GPR55 has been linked to energy homeostasis in different organs, its specific role in lipid metabolism in the liver and its contribution to the pathophysiology of nonalcoholic fatty liver disease (NAFLD) remains unknown. Approach and Results: We measured (1) GPR55 expression in the liver of patients with NAFLD compared with individuals without obesity and without liver disease, as well as animal models with steatosis and nonalcoholic steatohepatitis (NASH), and (2) the effects of LPI and genetic disruption of GPR55 in mice, human hepatocytes, and human hepatic stellate cells. Notably, we found that circulating LPI and liver expression of GPR55 were up‐regulated in patients with NASH. LPI induced adenosine monophosphate–activated protein kinase activation of acetyl–coenzyme A carboxylase (ACC) and increased lipid content in human hepatocytes and in the liver of treated mice by inducing de novo lipogenesis and decreasing β‐oxidation. The inhibition of GPR55 and ACCα blocked the effects of LPI, and the in vivo knockdown of GPR55 was sufficient to improve liver damage in mice fed a high‐fat diet and in mice fed a methionine‐choline–deficient diet. Finally, LPI promoted the initiation of hepatic stellate cell activation by stimulating GPR55 and activation of ACC. Conclusions: The LPI/GPR55 system plays a role in the development of NAFLD and NASH by activating ACC.